The Psychometric Properties of the Student–Teacher Relationship Measure for Omani Grade 7–11 Students - Aldhafri, Said; Alhadabi, Amal (Frontiers in Psychology, 2019)
Development and validation of a 25-item Student–Teacher Relationship Measure is described. It is a self-report measure estimating students’ perceptions of their relationship with teachers. The study was applied among adolescents in grades 7–11 in Oman. The measure was administered in Arabic. In Study 1, findings from exploratory factor analysis for 1,035 students indicated the presence of a 2-factor model (academic relation and social relation). In study 2, the confirmatory factor analysis results of 1,099 students supported study 1 results. High internal consistency was acquired. STRM was regarded as a reliable and potentially valid measure of the quality of student–teacher relationships.